1957
DOI: 10.1149/1.2428562
|View full text |Cite
|
Sign up to set email alerts
|

Tin Plating from the Pyrophosphate Bath

Abstract: The complex Sn2P~O7 bath was found satisfactory for the electroplating of Sn since it gave good quality deposits over a wide range of experimental conditions. Addition agents like dextrin-gelatin increased the brightness of the deposits. This bath has several advantages over the stannate bath.Acid sulfate and alkali stannate baths are widely used for industrial plating of Sn. In the literature, use of pyrophosphate baths is mentioned only by Roseleur (1-3) and Marino (4). Recently, Safranek and Faust (5) used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Early observations have also shown that tin plating could generally also be carried out with aqueous solutions of tin(II) salts containing pyrophosphate . In secondary literature of the early 19th century, it has been mentioned that, already in 1850, the “Roseleur solutions” obtained from stannous chloride and sodium pyrophosphate were found to be a potential source for tin plating. , This method was tested again by Vaid and Rama Char, who used the solution obtained from stannous pyrophosphate and sodium pyrophosphate, and reported “a complex being formed” . Because both copper(II) and zinc(II) also form soluble complexes with pyrophosphate in an intermediate pH region, the same system was applied in the electrodeposition of bronzes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early observations have also shown that tin plating could generally also be carried out with aqueous solutions of tin(II) salts containing pyrophosphate . In secondary literature of the early 19th century, it has been mentioned that, already in 1850, the “Roseleur solutions” obtained from stannous chloride and sodium pyrophosphate were found to be a potential source for tin plating. , This method was tested again by Vaid and Rama Char, who used the solution obtained from stannous pyrophosphate and sodium pyrophosphate, and reported “a complex being formed” . Because both copper(II) and zinc(II) also form soluble complexes with pyrophosphate in an intermediate pH region, the same system was applied in the electrodeposition of bronzes.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This method was tested again by Vaid and Rama Char, who used the solution obtained from stannous pyrophosphate and sodium pyrophosphate, and reported "a complex being formed". 8 Because both copper(II) 12 and zinc(II) 13 also form soluble complexes with pyrophosphate in an intermediate pH region, the same system was applied in the electrodeposition of bronzes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The continuous electrodeposition of tin was conducted on the resulting 3DC1, employing a pyrophosphate bath 10 (0.25 M Sn 2 P 2 O 7 + 1 M K 4 P 2 O 7 ) as the basic tin plating bath, together with polyethylene glycol (mean molecular weight 600: PEG600) and formaldehyde (HCHO) as additives.…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of pyrophosphate baths available in the literature [42]. These types of baths containing P 2 O 2 2-is considered as one of the most stable systems and is widely used for Sn plating [59,60]. However, its use is limited in literature due to one disadvantage, that it requires more control and maintenance than the other plating baths.…”
Section: Pyrophosphate Bathsmentioning
confidence: 99%
“…These baths require more control of the electrodeposition parameters. Normally chelating agents and organic additives such as triethanolamine, sodium gluconate, 1, 4-hydroxybenzene, and Triton X-100 have been added in pyrophosphate baths [42,59,60,61,81,82]. The additives are active only up to a certain concentration and have a beneficial effect on the microstructure of the deposits by increasing the cathodic polarization.…”
Section: Additivesmentioning
confidence: 99%